Qualitative Exploration of Death Education in Mainland China : Generating Design Considerations for a Culturally Relevant Curriculum Framework - Duan Shengyang, Duan; Lee, Jun Choi (Sciedu Press, 2025)
Death education has garnered increasing global attention for its role in enhancing emotional resilience, ethical awareness, and psychological preparedness, particularly in health and social sciences. However, in mainland China, its development remains constrained by deep-rooted cultural taboos and limited institutional support. This qualitative study explores design considerations for a culturally relevant death education curriculum within Chinese higher education. Semi-structured interviews and focus group discussions were conducted with 58 participants—including faculty, administrators, and students—from four universities across China. Thematic analysis revealed four core domains essential for effective curriculum development: (1) underlying principles, (2) content design, (3) organization and delivery, and (4) assessment and feedback. Findings emphasize the importance of cultural sensitivity, interdisciplinary integration, and participatory curriculum co-construction. The study contributes empirical evidence and practical strategies for embedding death education in ways that align with Chinese cultural norms and evolving educational needs, offering a robust foundation for future curriculum reform in this emerging field. Keywords: death education, Chinese higher education, curriculum design, Mainland China